Concept understanding profile of high school students on doppler effect and sound intensity levels - Silaban, Yohansen Frando Hadinata; Jumadi, Jumadi (Momentum: Physics Education Journal, 2022)
The purpose of this study is to map the profile of high school students' conceptual understanding in physics subjects with the Doppler effect and sound intensity levels, and to show the causes of misconceptions in high school students from the results of the Certainty of Response Index (CRI) method applied. The research method is descriptive quantitative with data analysis techniques in the form of descriptive statistics. The data collection technique used is an ordinary multiple choice test instrument equipped with a confidence level scale using the model CRI (Certainty of Response Index). This confidence scale is used as data for understanding students' concepts in answering questions that are analyzed statistically. The research subjects were 66 high school students in class XI who were randomly selected and had received lessons on sound waves. The test results showed that there were misconceptions in each item with the largest percentage of 45.45% in item number 3 and the smallest 12.12% in item number 2. Other responses in the form of lucky guess and not knowing the concept were also found with varying percentages. The misconceptions encountered occurred in the use of signs for the speed of the observer and the speed of the source, the relationship between distance and number of sound sources at the level of sound intensity, and the relationship between sound magnitudes. The results of this concept understanding profile are expected to be information for teachers to be able to overcome students' misconceptions and arrange appropriate learning strategies during the learning process.